Booms and systemic banking crises - Frederic Boissay; Fabrice Collard; Frank Smets (European Central Bank (ECB), 2013)
The empirical literature on systemic banking crises (SBCs) has shown that SBCs are rare events that break out in the midst of credit intensive booms and bring about particularly deep and long-lasting recessions. We attempt to explain these phenomena within a dynamic general equilibrium model featuring a non-trivial banking sector. In the model, banks are heterogeneous with respect to their intermediation skills, which gives rise to an interbank market. Moral hazard and asymmetric information on this market may generate sudden interbank market freezes, SBCs, credit crunches and, ultimately, severe recessions. Simulations of a calibrated version of the model indicate that typical SBCs break out in the midst of a credit boom generated by a sequence of positive supply shocks rather than being the outcome of a big negative wealth shock. We also show that the model can account for the relative severity of recessions with SBCs and their longer duration.
Keywords: E32; E44; G01; G21; 330; Asymmetric information; credit crunch; lending boom; Moral Hazard; systemic banking crisis